Listen, Draw, Understand: A Creative Approach to Teaching Listening Comprehension - Nabila Khalifatul Jannah; Aminah Aminah; Budi Budi; Anjar Kusuma Dewi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the effectiveness of the Listen-and-Draw technique in enhancing the listening comprehension of eighth-grade students at SMP Negeri 1 Banawa Tengah. Employing a quantitative approach and quasi-experimental design, two classes were selected: one experimental group taught using the Listen-and-Draw method and one control group taught with conventional instruction. Pretest and posttest assessments were administered to measure student achievement. The results indicated a significant improvement in the experimental group’s performance (mean posttest score = 47) compared to the control group (mean = 33). The t-test analysis (t-count = 9.97 > t-table = 0.0195) confirmed a statistically significant difference between groups. These findings support the use of the Listen-and-Draw technique as an effective instructional method to improve listening comprehension among junior high school students.